Navigating the Uncharted Waters: Exploring Challenges and Opportunities in Block chain-Enabled Cloud Computing for Future Research - Aashesh Kumar; Muhammad Fahad; Haroon Arif; Hafiz Khawar Hussain (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This article offers a thorough examination of the prospects, challenges, and future directions of block chain-enabled cloud computing, navigating a field that is still relatively new. The study explores the intricacies of the integration, from laying forth fundamental ideas to analyzing the present situation. Case studies shed light on effective implementations in the fields of finance, healthcare, supply chains, and other areas, offering insightful guidance for future initiatives. Examined are the transformative potential, security consequences, and regulatory considerations, highlighting the importance of sound frameworks and responsible development. Important factors including cooperation, sustainability, privacy, user education, regulatory clarity, and ongoing research are outlined in the roadmap for the future. In summary, the paper predicts a revolutionary digital future where block chain technology and cloud computing combine to foster creativity, cooperation, and resilience.